The maintenance of jetty terminal to Langkawi / Nor'ashikin Mat Hashim - Mat Hashim, Nor'ashikin (Faculty of Architecture, Planning and Surveying, 2015)
Langkawi, officially known as Langkawi the Jewel of Kedah is an archipelago of 104 islands in the Andaman Sea, some 30 km off the mainland coast of northwestern Malaysia . It can only be accessed by using air and water transport. Generally, there are three main jetty terminal function as jetty passenger terminal was built as the entrance through the waterway to Langkawi including Kuala Perlis Jetty Terminal, Kuala Kedah Jetty Terminal and Penang Jetty Terminal . The three terminal jetty is also under the administration and management of the Marine Department of Malaysia . In this study, three of the selected terminal is Kuala Perlis Jetty Terminal, Kuala Kedah Jetty Terminal and terminal Kuah Jetty Terminal. Langkawi will be visited by tourists, especially during international program like Langkawi International Maritime and Aerospace Exhibition (LIMA) and Le Tour de Langkawi . The attractiveness of a tourism center to Langkawi depending on the level of maintenance at the jetty terminal . The Maintenance of Jetty Terminal To Langkawi is selected as title of Academic Project II (BSS 658). This study has been conducted to achieve the following three objectives including to study the maintenance of jetty terminal, to identify the user perception and satisfaction with the maintenance of jetty terminal and to suggest improvements of facilities of jetty terminal. Distribution of the questionnaire was carried out to obtain the needed data is done on the three diffent terminal jetty involving respondents from ferry users and staff of the Marine Department of Malaysia . The data collected is then analyzed to determine whether the results of this study is successful or not achieving the objectives . All suggestions and criticisms regarding terminal jetty terminal is accounted for improvement for convenience of ferry users.